2018
DOI: 10.1111/phpp.12425
|View full text |Cite
|
Sign up to set email alerts
|

An international comparison of Google searches for sunscreen, sunburn, skin cancer, and melanoma: Current trends and public health implications

Abstract: Online skin cancer prevention campaigns should focus on the search terms sunburn and sunscreen, especially given the declining interest between 2004 and 2016 in the terms skin cancer and melanoma seen in multiple countries. Search term interests varied with melanoma outcomes and between countries, suggesting the importance of customizing approaches based on local population interests and geographic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Peaks of SVIs for breast cancer matched the Breast Cancer Awareness Month (pink October, pink ribbon) and for prostate cancer the trendy “Movember” campaign. Our results confirm that awareness campaigns provide a boost at the peak time of interest [4, 7]. …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Peaks of SVIs for breast cancer matched the Breast Cancer Awareness Month (pink October, pink ribbon) and for prostate cancer the trendy “Movember” campaign. Our results confirm that awareness campaigns provide a boost at the peak time of interest [4, 7]. …”
Section: Discussionsupporting
confidence: 78%
“…It is used as a research tool to analyze the interest of the general population in medical conditions [2]. It has already been applied for melanoma and skin cancers [3, 4]. Bloom et al [3] found an increase in the general populations’ interest in learning about skin cancer during summer months in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers studied mental health [53] and depression [54] queries. Other topics studied using GT data are skin cancer [55], sunscreen use [56], sunburn [57], seasonality of bruxism [58], multiple sclerosis [59], cancer [60], stroke [61], HIV [62], lupus [63], norovirus [64], sepsis [65], pertussis [66], epistaxis [67], plague [68], rheumatoid arthritis [69], and prostate cancer [70]. In terms of general population behavior, research was done using GT data on pharmaceutical data [71], vaccinations [72], movement disorders [73], digital epidemiology [74], kidney stone surgery [75], foot and ankle pain [76], knee injuries [77], osteoarthritis [78], seasonality of cellulitis [79], tracking influenza epidemics using climate data [80], palliative care [81], cosmetic body procedures [82], and anesthesia [83].…”
Section: Introductionmentioning
confidence: 99%
“…Google Trends® is a free tool provided by Google Inc that is easily accessible to the public to analyze search volumes according to user‐defined search terms with data on geographical and temporal trends. In Dermatology, these trends have been analyzed to assess public interest in skin diseases, dermatitis, esthetic plastic surgery, skin cancer, Mohs micrographic surgery, sunscreen, tanning, and hidradenitis suppurativa …”
Section: Introductionmentioning
confidence: 99%
“…In Dermatology, these trends have been analyzed to assess public interest in skin diseases, dermatitis, esthetic plastic surgery, skin cancer, Mohs micrographic surgery, sunscreen, tanning, and hidradenitis suppurativa. [6][7][8][9][10][11][12][13][14][15][16] The worldwide search interest in "sunscreen" has been generally increasing since 2008 with a waning trend for the search term "tanning bed." 15 In the United States of America, Google Trends® found that melanoma incidence was positively associated with searches for "sunscreen" and "sunburn" and negatively associated with "skin cancer" searches.…”
Section: Introductionmentioning
confidence: 99%